V.P.TSESSEVICH - A SCIENTIFIC SUPERVISOR OF THE ODESSA OBSERVATORY EXPEDITION ON THE DETERMINATION OF LATITUDE AND LONGITUDE FOR BTA POSITION SITE - Volyanskaya, M. Yu.; Mandel, E.; Russo, Yu. D. (Одеські астрономічні публікації, 2017)
In the paper one from little known pages of Prof. V.P.Tsessevich’ life and scientific activity as an organizer and scientifics supervisor of expedition on the determination of coordinates of site, where BTA would be placed, is described. V.P.Tsessevich have formed a staff of expedition, scientific problems and have taken direct part of the first and final stages of the expedition. As a result of expedition coordinates which corresponded to requirements of astroplace of the second class (expeditionary) have been obtained and axes of BTA have been traced on the locality.